2015
DOI: 10.3904/kjim.2015.30.1.88
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of low-dose transdermal fentanyl in opioid-naïve cancer patients with moderate-to-severe pain

Abstract: Background/AimsLittle is known about the efficacy of low-dose transdermal fentanyl (TDF) patches in opioid-naïve patients with moderate-to-severe cancer pain.MethodsThis study had an open-label, prospective design, and was conducted between April 2007 and February 2009 in seven tertiary cancer hospitals; 98 patients were enrolled. TDF was started using a low-dose formulation (12.5 µg/hr), and the dose was adjusted according to the clinical situation of individual patients. Pain intensity, the TDF doses used, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Among the new susceptibility loci identified by Gormley et al (Gormley et al 2016 ) and included in our GRS, two lie in or near genes involved in regulation of vascular tone ( MEF2D, DOCK4, and SLC24A3 ) (Dong et al 2006 ; Firulli et al 1996 ; Kang et al 2015 ), while ARMS2, PHACTR1, TGFBR2, LRP1, and NOTCH4 have been previously associated with vascular disease (Delev et al 2017 ; Beaudoin et al 2015 ; Guo et al 2016 ; Hayashi et al 2010 ; Yang et al 2016 ), consistently with the suggested role of vascular dysfunction in migraine pathogenesis. Interestingly, one of the novel migraine-associated SNPs included in our GRS, rs75213074, is located near NLRP1 , which encodes for the sensor component of an inflammasome (a protein complex that activates caspases and cytokines in response to damage-associated signals) (Guo et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the new susceptibility loci identified by Gormley et al (Gormley et al 2016 ) and included in our GRS, two lie in or near genes involved in regulation of vascular tone ( MEF2D, DOCK4, and SLC24A3 ) (Dong et al 2006 ; Firulli et al 1996 ; Kang et al 2015 ), while ARMS2, PHACTR1, TGFBR2, LRP1, and NOTCH4 have been previously associated with vascular disease (Delev et al 2017 ; Beaudoin et al 2015 ; Guo et al 2016 ; Hayashi et al 2010 ; Yang et al 2016 ), consistently with the suggested role of vascular dysfunction in migraine pathogenesis. Interestingly, one of the novel migraine-associated SNPs included in our GRS, rs75213074, is located near NLRP1 , which encodes for the sensor component of an inflammasome (a protein complex that activates caspases and cytokines in response to damage-associated signals) (Guo et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found patients who received tramadol experienced significantly less dry mouth compared to those who received morphine. Previous studies showed a large variation (1%–94%) in the occurrence of dry mouth [ 17 , 18 ]. Studies with low incidence rates documented only opioids-related adverse events spontaneously reported by patients without systematic assessment [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Singla y colegas (17) señalan que en el tratamiento con fentanyl del dolor por encima de cuatro en la EVA, la somnolencia puede aparecer de 30-50%. Kang y su equipo (18) , reportan que la somnolencia puede ser prevenida mediante la disminución de las dosis de medicamento. Unlü (19) demuestra en su investigación que el tratamiento con opiáceos no afecta el proceso cognitivo a pesar de que puede ocasionar somnolencia en algunos pacientes.…”
Section: Las Modalidades Terapéuticas Fueronunclassified